Psychopathological status, behavior problems, and family adjustment of Kuwaiti children whose fathers were involved in the first gulf war - Ohaeri Jude U; Al-Turkait Fawziyah A (BMC, 2008)
Abstract Objectives Following the end of the Gulf War that resulted in the liberation of Kuwait, there are no reports on the impact of veterans' traumatic exposure and posttraumatic stress disorder (PTSD) on their children. We compared the severity of anxiety, depression, deviant behavior and poor family adjustment among the children of a stratified random sample of four groups of Kuwaiti military men, viz: the retired; an active -in-the-army group (AIA) (involved in duties at the rear); an in-battle group (IB) (involved in combat); and a prisoners -of- war (POWs) group. Also, we assessed the association of father's PTSD/combat status and mother's characteristics with child psychosocial outcomes. Method Subjects were interviewed at home, 6 years after the war, using: the Child Behavior Index to assess anxiety, depression, and adaptive behavior; Rutter Scale A2 for deviant behavior; and Family Adjustment Device for adjustment at home. Both parents were assessed for PTSD. Results The 489 offspring (250 m, 239 f; mean age 13.8 yrs) belonged to 166 father-mother pairs. Children of POWs tended to have higher anxiety, depression, and abnormal behavior scores. Those whose fathers had PTSD had significantly higher depression scores. However, children of fathers with both PTSD and POW status (N = 43) did not have significantly different outcome scores than the other father PTSD/combat status groups. Mother's PTSD, anxiety, depression and social status were significantly associated with all the child outcome variables. Parental age, child's age and child's level of education were significant covariates. Although children with both parents having PTSD had significantly higher anxiety/depression scores, the mother's anxiety was the most frequent and important predictor of child outcome variables. The frequency of abnormal test scores was: 14% for anxiety/depression, and 17% for deviant behavior. Conclusion Our findings support the impression that child emotional experiences in vulnerable family situations transcend culture and are associated with the particular behavior of significant adults in the child's life. The primacy of the mother's influence has implications for interventions to improve the psychological functioning of children in such families. Mental health education for these families has the potential to help those in difficulty.